PENGELOLAAN HUTAN OLEH DAYAK HALONG MERATUS (Studi Kasus Masyarakat Adat Dayak Halong Desa Uren Kabupaten Balangan Provinsi Kalimantan Selatan) - Lina Tabitha Mandala; Kissinger Kissinger; Emmy Sri Mahreda; Hafizianor Hafizianor (EnviroScienteae, 2022)
This research aims to analyze Forest Management by the Indigenous People of Dayak Uren Village. This research was conducted at Uren Village, Halong District, Balangan Regency. The research location was selected using a purposive method. The object of research is the Dayak Uren indigenous people, Halong District, Balangan Regency. This research uses a qualitative approach. The results of this research indicate that community institutions in managing the Uren Village forest consist of two institutions, namely customary institutions and forest village management institutions. In managing the forest, the Dayak indigenous people of Uren Village have customary law which is divided into customary law in agriculture or plantations, hunting, utilizing plants, utilizing water sources, and managing forests as environmental services. According to customary law, the forest area of Uren Village is divided into three areas, namely the sacred forest area, the customary forest area, and the cultivation area. In addition, the Uren Dayak Indigenous People still believe in the ‘pamali’ tradition or taboos related to forest use. The mechanism for processing forest land for food purposes is to use a land clearing system that still uses the traditional method, namely logging, slashing, and burning using simple tools. The Uren Dayak Indigenous People also hold rituals related to religious tradition as a form of respect for the God, ancestors, and the goddess of rice. Forest management is an economic and ecological added value for the Dayak indigenous people of Uren Village. The availability of land to be used can make Uren Village have food security.